Religiosity as a factor of socio-psychological adaptation - Chanchykov, Ilya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is devoted to clarify the binding forces between religiosity and psychosocial adaptation. We analyzed the approaches of different scholars on the definition of "religion" category. The author focuses on exactly what components of religiosity can improve the social and psychological adaptation.